Preliminary simulation model toward the study of the effects caused by different mandibular advancement devices in OSAS treatment. Issue 13 (3rd October 2018) - Brunzini, Agnese; Gracco, Antonio; Mazzoli, Alida; Mandolini, Marco; Manieri, Steve; Germani, Michele
Abstract: The paper aims to evaluate the effects caused by a Mandibular Advancement Device (MAD) for Obstructive Sleep Apnoea Syndrome (OSAS) treatment. This study is based on Finite Element Method (FEM) for evaluating the load distribution on temporomandibular joint, especially on the mandibular condyle and disc, and on periodontal ligaments. The stress values on condyle and periodontal ligaments lead authors to consider MAD a safe procedure even for a long period. The obtained results also show the relationship between MAD material and load distribution at the periodontal ligaments. The paper is a step toward future analyses for studying and comparing the effects of MAD features, such as material, shape and dimensions, in order to allow the clinician prescribing the most fitting device.